Analysis of The Influence of Visible Safety Leadership and Job Satisfaction on Safety Work Performance at PT. Solusi Bangun Indonesia Tbk Pabrik Cilacap - Sugiarto, Sugiarto; Syahyunan, Syahyunan; Fauzan Azhmy, Muhammad (Sumber Belajar Sejahtera, 2025)
This research aims to analyze the influence of visible safety leadership and job satisfaction on safety work performance at PT. Solusi Bangun Indonesia Tbk Cilacap Factory. This research uses quantitative research methods with descriptive and analytical approaches. The research subjects were employees and contractors of PT. Solusi Bangun Indonesia Tbk Cilacap Factory involved in overhaul activities. Data collection was carried out randomly through questionnaires, interviews and observations. Research data was analyzed using quantitative statistical test techniques and then described in detail based on the results of each test. The research results show that work accidents at PT. Solusi Bangun Indonesia decreased during the 2023 overhaul activities due to its leadership role in ensuring workplace safety during these activities. This research highlights how visible leadership behavior in the field, or visible safety leadership and job satisfaction, contributes to increasing safety work performance. The Regression and Correlation Test Method used to analyze the data shows that 76.4% of safety work performance is influenced by visible safety leadership and job satisfaction, while the rest is influenced 23,6 % by other factors. These results confirm that leadership behavior that is proactively involved and visible in the field and high job satisfaction in implementing safety has a significant impact on safety performance, which ultimately contributes to a safer work environment for all workers.